2012
DOI: 10.1007/s11255-012-0289-7
|View full text |Cite
|
Sign up to set email alerts
|

The kidney in space

Abstract: Renal adaptation in space has been studied during various space missions since the early 70s. Technical and financial disadvantages of performing experiments under real microgravity conditions have warranted the conductance of relative studies under simulated weightlessness on earth. Arriving in microgravity leads to a redistribution of body fluids to the upper part of the body and an exaggerated extravasation very early in-flight. Plasma volume as well as skin evaporation and oral hydration are reduced, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
0
14
0
2
Order By: Relevance
“…In addition, during a Mars simulation study in humans, the hormones aldosterone and cortisol fluctuated for longer-than-usual periods despite constant salt intake, suggesting that clock genes may be involved in water–mineral balance [ 47 ]. Few studies have examined the responses of adrenal glands and kidneys in spaceflight [ 45 , 47 , 48 , 49 , 50 , 51 ]. Therefore, our observed asynchrony of clock genes in these three tissues may provide new molecular-level insights about the endocrine systems and water–mineral balance regulation during spaceflight.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, during a Mars simulation study in humans, the hormones aldosterone and cortisol fluctuated for longer-than-usual periods despite constant salt intake, suggesting that clock genes may be involved in water–mineral balance [ 47 ]. Few studies have examined the responses of adrenal glands and kidneys in spaceflight [ 45 , 47 , 48 , 49 , 50 , 51 ]. Therefore, our observed asynchrony of clock genes in these three tissues may provide new molecular-level insights about the endocrine systems and water–mineral balance regulation during spaceflight.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting evidence came from recent studies that suggested major roles of immunity and energy/lipid metabolism on spaceflight-induced stress. 27 , 70 , 71 We could further expand our knowledge by following up to target the cell lines with in vitro assays linked to immunity, 72 kidney, 73 and liver 71 functions that are important to spaceflight-induced stress. In fact, our forthcoming study will particularly focus on the role of immunity and metabolism in the potential bone loss in vitro during spaceflight.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increased incidence of spaceflight-associated dehydration and hypercalciuria, thereby increasing the risk of calcium oxalate stones in both female and male astronauts. 59 While the overall incidence is not much different from that found on Earth, urinary tract infections in space are more common in women and have been successfully treated with antibiotics. 60 Transient difficulties with urination are reported by both sexes, but the only astronauts requiring catheterization have been women.…”
Section: Reproductivementioning
confidence: 99%